ANALISIS FAKTOR CEMARAN SUMUR TERHADAP KEJADIAN HEPATITIS A DI KECAMATAN NGADIROJO KABUPATEN PACITAN - Setiani, Isna Wahyu; Kriswandana, Ferry; Rachmaniyah, Rachmaniyah (Poltekkes Kemenkes Tanjung Karang, 2020)
Hepatitis A is a fecal oral disease which is still a public health problem in Indonesia. The Pacitan Regency Government has determined an extraordinary event (KLB) of Hepatitis A since June 25th, 2019, there were 1,310 confirmed cases. This research aims to determine the relation between well contamination and the incidence of Hepatitis A.This study used a case control design by means of observation and measurement of 36 dug wells randomly selected from 18 cases and 18 controls based on inclusion criteria. The water microbiology examination was carried out at the Surabaya Health Polytechnic Laboratory with the Most Probable Number (MPN) method, and the data analysis technique used was the serial point coefficient correlation.The results suggested that all observed well water was contaminated by E. coli bacteria, and more than half of them did not meet the construction requirements, namely from the aspect of distance from pollutant sources, walls, lips and well floors. The analysis results suggested a relation between Escherichia coli contamination and well construction (p-value = 0.036). However, it did not show a significant relation with the incidence of Hepatitis A (p-Value = 0.514).Improved well construction, increased knowledge, and hygiene behavior are efforts of which must be made in managing Hepatitis A.Â